A importância dos fósseis para o ensino de evolução: uma proposta de sequência didática promovendo o conhecimento da paleofauna brasileira - Júlio Antônio Alvarenga Santos (2023)
The classification of Cerrado phytophysiognomies is challenging due to the lack of clear distinction between them. To assist in this distinction and understand the influence of edaphic factors, we analyzed the floristic composition, diversity and structure of tree communities in the Serra do Cipó National Park. We used data from three 1ha plots of different Cerrado phytophysiognomies and information from NeoTropTree, totaling 558 sites. We analyzed 21 edaphic parameters and used multivariate analyses, species accumulation curves, Venn diagrams, statistical tests for comparison of means and usual phytosociological parameters. We confirmed the floristic distinction of Serra do Cipó phytophysiognomies in three vegetation types previously observed for the Cerrado (mesotrophic cerrado, dystrophic cerrado sensu largo and rupicolous cerrado). We identified distinct patterns in richness, diversity and structure, with greater species richness and diversity in forest physiognomies (mesotrophic cerrado) compared to savannas (dystrophic cerrado and rupicolous cerrado). Descriptors such as the Shannon index and basal area proved to be effective in differentiating the physiognomies. The vegetation types of the Cerrado in Serra do Cipó are grouped into three floristic groups influenced by edaphic variables. Remaining phosphorus is the main variable in the compositional structuring of the physiognomies, and this study is a pioneer in demonstrating the importance of this variable in distinguishing the physiognomies. Our findings fill a gap in studies, allowing a detailed view of the characteristics and responses of the physiognomies to specific environmental factors, and provide new and important information for the conservation biogeography of the Cerrado.